Fifteen Years Since the World Summit on the Information Society - United Nations Conference on Trade; Development (United Nations, 2020)
In 2005, the international community gathered in Tunis for the second and final session of the World Summit on the Information Society (WSIS). That gathering concluded a process, begun in 1998, to build global understanding of the growing importance of information and communication technologies (ICTs) in many aspects of economy and society. WSIS established a vision for the international multistakeholder community of ‘a people-centred, inclusive and development-oriented Information Society, where everyone can create, access, utilize and share information and knowledge’ to promote sustainable development in their communities and improve their quality of life. Enormous change has taken place since then. ICTs will play a substantial role in delivering the SDGs. This report summarises developments and suggests priorities for the assessment to be made in five years’ time.